Back Cover. Issue 6 (15th February 2022) - Unknown
Abstract : This cover picture shows a visible‐light promoted tandem radical cascade cyclization/arylation of quinoxalin‐2(1 H )‐ones with bromodifluoroacetamides, which provides a simple and efficient method for the building of α, α ‐difluoro‐ γ ‐lactam‐fused quinoxalin‐2(1 H )‐ones. For more details please see the given article by Zhou et al . on page 713—718. Abstract : This cover picture shows a visible‐light promoted tandem radical cascade cyclization/arylation of quinoxalin‐2(1 H )‐ones with bromodifluoroacetamides, which provides a simple and efficient method for the building of α, α ‐difluoro‐ γ ‐lactam‐fused quinoxalin‐2(1 H )‐ones. For more details please see the given article by Zhou et al . on page 713—718.